Improving Cognitive Function in Elderly with Dementia through Art Therapy and Brain Gym in Gunungpati, Semarang - Novita Wulan Sari; Margiyati Margiyati; Candra Herzegovina (International Journal Of Health Science, 2025)
Dementia is a condition that occurs in the elderly where they experience a decrease in the function of consciousness so that the ability to process thoughts is progressively damaged. Cognitive function is a human mental process that includes perception, attention, knowledge, thought processes, and memory, due to the aging process. Art therapy is a therapy that aims to help overcome a number of mental health disorders and psychological stress in the elderly who experience decreased cognitive function. Brain gym to reduce cognitive function due to aging and as a form of stimulation to improve brain abilities in the elderly. The purpose of this case study is to describe the application of art therapy and brain gym to improve cognitive function in the elderly with dementia in the target area of the Gunungpati Health Center, Semarang. The case study method used is descriptive with a case study approach. Subjects used were 2 women and men with dementia, aged 60-74 years, lived with family, could be invited to communicate verbally, and declined experienced cognitive function, with MMSE (Mini Mental State Examination): score 17-23 which is said to be probable cognitive impairment, and can read and write with a duration of 20-30 minutes. The results of the case study showed that Subject I experienced an increase in cognitive function from a score of 23 to 26, and Subject II from a score of 24 to 27. Application of art therapy and brain gym to improve cognitive function in the elderly with dementia is recommended as a nursing intervention in the management of family members with dementia.